Correction to: Status of racial disparities between black and white women undergoing assisted reproductive technology in the US - David B. Seifer; Burcin Simsek; Ethan Wantman; Alexander M. Kotlyar (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.